MANAGEMENT OF SCABIES PATIENT WITH SECONDARY INFECTION IN 7 YEARS OLD BOYS - Hamzah, Rizqa Atina Mira (Jurnal Agromedicine Unila: Jurnal Kesehatan dan Agromedicine, 2014)
Scabies is a skin disease caused by Sarcoptes scabiei mites infection. Progression of the disease is also influenced by low socio economic circumstances, poor level hygiene, lack of knowledge, and also diagnosis and treatment errors. internal and external factors identification of patient relating to personal hygiene behavior. This study is a case report, primary data obtained through anamnesis (autoanamnesis and alloanamnesis), physical examination, and laboratory tests in Puskesmas. Home visits, completing the family data, psychosocial, and also environment. Assessment based on early holistic diagnostic, process, and end of study by quantitative and qualitative. A boy, 7 years old, has a habit of sharing clothes and towels, and living in a dirty home environment. Based on the theory, case of scabies with secondary infection is a problem on hygine and healthy living behavior. Family medicine has an important role in scabies patient management with secondary infection and need parents role to solve problems and modify family habits. [J Agromed Unila 2014; 1(2): 151-155] Keywords: family medicine care, personal hygiene, scabies